Hemorrhagic Shock Status in ZAGAZIG Maternity University Hospital: Prognosis and Risk Factors - Helal, Khaled Fathy; Fahmy, Mohamed El Sayed (Archives of Clinical and Medical Case Reports, 2019)
Objective: to assess the frequency and prognosis of hemorrhagic shock states in obstetrics in ZAGAZIG maternity university hospital. Methods: a prospective study with descriptive and analytical purpose, carried out from January 1 to September 30, 2018 in ZAGAZIG maternity university hospital. Results: We registered 1944 obstetrical emergencies. Among those emergencies, hemorrhagic shock status was diagnosed in 61 female patients, i.e. a hospital-based frequency estimated at 3.1%. Patients’ mean age was 27.0 ± 6.3 years. 26.2% of those patients were between 20 and 24 years old. The mortality rate of hemorrhagic shock was 11.5%. All causes combined, if we consider the 16 deaths registered in the medical unit during the same time period, the share of mortality associated with hemorrhagic shock was 43.75%. After adjustment, the risk factors significantly associated with maternal death cases were uterine rupture (p=0.0000), coagulation disorders (p=0.0000) and Glasgow score below 9 (p=0.0285). Conclusion: Obstetrical hemorrhagic shock was common in ZAGAZIG maternity university hospital. Its lethality is very high despite multidisciplinary management, hence the importance of early and adequate management of hemorrhage.